2021
DOI: 10.3389/fcimb.2021.639065
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plasmodium falciparum Pantothenate Kinase and Identification of Its Inhibitors From Natural Products

Abstract: Coenzyme A (CoA) is a well-known cofactor that plays an essential role in many metabolic reactions in all organisms. In Plasmodium falciparum, the most deadly among Plasmodium species that cause malaria, CoA and its biosynthetic pathway have been proven to be indispensable. The first and rate-limiting reaction in the CoA biosynthetic pathway is catalyzed by two putative pantothenate kinases (PfPanK1 and 2) in this parasite. Here we produced, purified, and biochemically characterized recombinant PfPanK1 for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 61 publications
(94 reference statements)
1
16
0
Order By: Relevance
“…Studies in rodent malaria parasites have highlighted that single-copy PPCS and PPCDC are also dispensable [ 21 , 50 ]. The ability of PanK to phosphorylate pantetheine [ 61 ] points toward a possible salvage of pantetheine for CoA synthesis ( Fig 1 ), similar to observations in some bacteria [ 62 ], potentially rendering PPCS and PPCDC dispensable. Nevertheless, the presence of pantetheine-hydrolyzing enzymes, pantetheinases (vanins), in the serum possibly limits the amount of freely available pantetheine.…”
Section: Introductionsupporting
confidence: 59%
“…Studies in rodent malaria parasites have highlighted that single-copy PPCS and PPCDC are also dispensable [ 21 , 50 ]. The ability of PanK to phosphorylate pantetheine [ 61 ] points toward a possible salvage of pantetheine for CoA synthesis ( Fig 1 ), similar to observations in some bacteria [ 62 ], potentially rendering PPCS and PPCDC dispensable. Nevertheless, the presence of pantetheine-hydrolyzing enzymes, pantetheinases (vanins), in the serum possibly limits the amount of freely available pantetheine.…”
Section: Introductionsupporting
confidence: 59%
“…gondii , coupled with the intense investigation of this pathway as a drug target in P . falciparum [ 27 , 39 41 , 52 67 ], suggests that further characterisation of Tg PanK, and the CoA biosynthesis pathway in T . gondii , could yield novel drug targets for chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several attempts by us [unpublished] and others [37][38][39][40][41] to express a functional PfPanK1. Whilst the protein has been successfully expressed in soluble form using various heterologous expression systems (Escherichia coli, insect cells, Saccharomyces cerevisiae), until recently [41], no study had reported PanK activity from the heterologously-expressed and purified protein. Nurkanto et al [41] have recently reported the functional expression of PfPanK1 in E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations